PENGARUH INSENTIF, KEPEMIMPINAN SERTA LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA UD. SARI DAUN NGANJUK - Saputra, Dhiki Hendra; Bhirawa, Sigit Wisnu Setya; Meilina, Restin (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
Sari Daun Nganjuk is a clove processing industry in Nganjuk which was established in 2010. UD. Sari Daun Nganjuk is a company that oversees rural products, especially those that use dried clove leaves by distillation of dry clove leaves using steam purification. at the UD processing plant. Sari Daun Nganjuk found several human resource problems such as initiative, leadership and the work environment that are still under-appreciated at UD. The leaf juice is drooping. This study aims to be used properly by UD. Sari Daun Nganjuk as a source of perspective to promote the presentation of UD's performance. The leaf juice is drooping. This study examines whether there is an influence between incentives, leadership and work environment on the performance of UD. The leaf juice is drooping. processing information in the results of the study indicate that the factors of incentives, leadership and work environment greatly affect the performance of UD employees. The leaf juice is drooping. it is known that the research uses a reliability coefficient with a value of 68.2%, representative performance is influenced by the strength of incentives, leadership and work environment, with the remaining 31.8% influenced by various elements not identified in this assessment.